Administration and patient-incurred costs associated with opioid agonist treatment in Norway. (2nd November 2022) - Pedersen, Mikkel H.; Danø, Anne; Gibbons, Carl; Jensen, Rasmus
Abstract: Objectives: Opioid use disorder is associated with high rates of mortality and has become an escalating global health issue. Opioid agonist treatment (OAT) with oral methadone or daily sublingual buprenorphine hydrochloride, either administered separately or in combination with naloxone hydrochloride (SL-BPN, SL-BPN/NX), is supervised by a healthcare professional experienced in treating opioid use disorder to ensure proper dosing and prevent misuse. For that reason, there may be substantial direct and indirect costs associated with OAT. Recently, weekly and monthly subcutaneous depot formulations of buprenorphine (SC-BPN) have been approved. This study aimed to estimate management and patient-incurred costs associated with the most commonly used OATs compared to the cost of weekly and monthly SC-BPN. Methods: We conducted a cost-minimisation analysis comparing the monthly costs of OAT treatment with oral formulations, i.e. oral methadone, SL-BPN, SL-BPN/NX and SC-BPN. The analysis assessed treatment acquisition costs and costs associated with management, supervision and administration of therapy, patients' transportation costs and the indirect costs associated with patients' time-use. The model was set up to reflect the Norwegian medically assisted rehabilitation system and considered the costs of a stable maintenance OAT regimen given continuously to patients already initiated and titrated on the therapy. Results: OAT management with monthly formulation of SC-BPN was associated with a reduction in monthly costs of €605, €586, and €411 per month compared to SL-BPN, SL-BPN/NX and oral methadone, respectively. Similar results were estimated when comparing to the weekly formulation of SC-BPN. Conclusion: The analysis showed that the monthly formulation of SC-BPN was the cost-minimising alternative, followed by the weekly formulation, when considering all cost components.